HIV-related tuberculosis: mortality risk in persons without vs. with culture-confirmed disease - Crabtree-Ramírez, B. (Int J Tuberc Lung Dis, 2019)
BACKGROUND: Tuberculosis (TB) diagnosis in human immunodeficiency virus (HIV) positive persons is difficult, particularly in resource-limited settings. The relationship between TB culture status and mortality in HIV-positive persons treated for TB is unclear. METHODS: We evaluated HIV-positive adults treated for TB at or after their first HIV clinic visit in Argentina, Brazil, Chile, Honduras, Mexico or Peru from 2000 to 2015. Anti-tuberculosis treatment included 2 months of isoniazid, rifampicin (RMP)/rifabutin (RBT), pyrazinamide ± ethambutol, followed by continuation phase treatment with isoniazid + RMP/RBT. RESULTS: Of 759 TB-HIV patients, 238 (31%) were culture-negative, 228 (30%) had unknown culture status or did not undergo culture and 293 (39%) were culturepositive. The median CD4 at TB diagnosis was 96 (interquartile range 40–228); 636 (84%) received concurrent antiretroviral therapy (ART) and antituberculosis treatment. There were 123 (16%) deaths: 90/466 (19%) with TB culture-negative, unknown or not performed vs. 33/293 (11%) who were TB culturepositive (P=0.005). In Kaplan-Meier analysis, mortality in TB patients without culture-confirmed disease was higher (P = 0.002). In a Cox model adjusted for age, sex, CD4, ART timing, disease site and stratified by study site, mortality in persons without culture-confirmed TB was not significantly increased compared to those with culture-positive TB (hazard ratio 1.39, 95%CI 0.89–2.16, P = 0.15). CONCLUSION: Most HIV-positive patients treated for TB did not have culture-confirmed TB, and mortality tended to be higher in patients without culture-confirmed disease, although the association was not statistically different after adjusting for other variables. Accurate TB diagnosis in HIV-positive persons is crucial.